Transition to Adulthood: Leaving the Parental Home in the Last Soviet and the First Post-Soviet Generation - Daukšaitė, Laura (Sociologija. Mintis ir veiksmas, 2019)
The article presents a research on trajectories of leaving the parental home in the last Soviet and the first post-Soviet generations. It focuses on social transformation of the state during the transition from the Soviet to the post-Soviet and its impact on the life-course of these generations. In our study, we applied a dyadic approach and conducted semi-structured interviews with women of the last Soviet generation (born in 1962–1972) and their children (born in 1992–2002), who represent the first post-Soviet generation. Early changes in and the differentiation of the timetable of transition to adulthood of the last Soviet generation indicated a declining effect of ideologically supported social structures on the life-course of young adults and the growing power of individual decision to leave the parental home or stay within. The rapidly increasing globalization and a transformed economy shaped a new structural environment for the coming of age for the first post-Soviet generation; therefore, we can interpret the further pluralization, de-standardization, and differentiation of the timetable of the transition to adulthood of this generation as a reaction of young people to the emerging risks and insecurities.